Labial adhesion in children at the Jos University Teaching Hospital - Ephraim Samuels; Amaka Ngozi Ocheke; Nathaniel E. O. Samuels (Wolters Kluwer Medknow Publications, 2016)
Background: Labial adhesion is one of the most common reasons for gynaecologic consultations in children. We sought to determine the prevalence of labial adhesions, mode of presentation and treatment in children at the Jos University Teaching Hospital. Materials and Methods: A retrospective study of labial adhesions in children from January 2004 to December 2013. Data on paediatric gynaecological consultations, and labial adhesions were retrieved from the gynaecological clinic and the theatre records. The case notes of those with labial adhesions were retrieved and the relevant data extracted. Results: The total number of paediatric patients seen at the gynaecology clinic over the study period was 379 and 25 had labial adhesion (6.6%). The majority (88%) presented in the first 2 years of life, all the patients were asymptomatic, and 2 (8%) had surgical separation of the adhesions while the rest were managed conservatively. A total of 5 (20%) came for follow-up. While 2 (8%) came a week later following surgical management, 3 (12%) came back more than 6 months later due to recurrence following conservative management. Conclusion: Labial adhesions account for significant proportion of paediatric gynaecologic consultations. They are usually asymptomatic, occur in the first 2 years of life and frequently managed conservatively.